Reversals of Fortune? A Long-term Perspective on Global Economic Prospects (2013)
It is conventional wisdom that:Continued fast growth in the BRICS will result in a rapid catch-up to match and even surpass Western income levels in the next few decadesThe crisis in Europe will soon be over and normal growth will then resume as if nothing had happenedThe tax competition resulting from globalization means a race to the bottom in which corporate tax rates fall dramatically everywhereThe best way to escape the poverty trap is to give the poor more moneyLosers from globalization can be ignored by politicians in western democracies because they do not matter for electoral outcomesThe adjustment problems for developing countries arising from the crisis are quite minor and easy to deal withActually, as Reversals of Fortune shows, all of these beliefs are highly questionable. The research findings reported here provide economic analysis and evidence that challenge these claims.In the report, Nicholas Crafts asks: "What Difference does the Crisis make to Long-term West European Growth?"  Vera Troeger considers "The Impact of Globalisation and Global Economic Crises on Social Cohesion and Attitudes towards Welfare State Policies in Developed Western Democracies."  Stephen Broadberry looks at "The BRICs: What does Economic History say about their Growth Prospects?"  Sharun Mukand takes "The View from the Developing World: Institutions, Global Shocks and Economic Adjustment."  Finally, Sayantan Ghosal has a new perspective on "The Design of Pro-poor Policies."